The Dynamics of Bullying in Schools: Causes, Impacts, and Prevention Strategies - Jumra; Mukhawas Rasyid; Andi Baharuddin; Arifullah (Journal of Indonesian Scholars for Social Research, 2025)
Bullying in schools is a persistent social issue that significantly impacts students’ psychological well-being, academic performance, and overall development. This study aims to analyze the dynamics of bullying by exploring its underlying causes, the consequences for both victims and perpetrators, and the most effective prevention strategies in educational settings. Using a literature review approach, this research synthesizes findings from various academic sources to provide a comprehensive understanding of school bullying. The results indicate that bullying arises from multiple interconnected factors, including individual traits, family environment, peer influence, and school policies. Victims often suffer from long-term psychological effects such as anxiety, depression, and low self-esteem, which can lead to decreased academic motivation and social withdrawal. Meanwhile, perpetrators may develop aggressive tendencies that persist into adulthood, increasing the likelihood of engaging in antisocial behavior. Moreover, bullying negatively affects the overall school climate, creating an unsafe learning environment that disrupts students' educational experiences. To address this issue, schools must implement a multifaceted prevention approach, including educational campaigns, strict anti-bullying policies, teacher training programs, and parental involvement. Establishing a supportive and inclusive school culture is essential to reducing bullying incidents and fostering positive student interactions. By incorporating these strategies, schools can create a safer and more conducive learning environment that promotes student well-being and academic success.